"Employment precariousness" in a European cross-national perspective. A sociological review of thirty years of research - Barbier, Jean-Claude (Paris, 2011)
"What has been analysed in France mainly under the term "précarité de l'emploi" over the past 30 years was mostly dealt with differently in other countries (atypical, non-standard employment). Research on these issues dates back to the 1970s in sociology and institutional economics. More recently some political scientists have endeavoured to link up the labour market theme with developments in systems of social protection and they are talking about "dualism" and "dualization". Despite the constant intellectual investment put into the topic, it is striking that indicators for comparative measurement of the phenomenon have remained rather unsophisticated, as the basic opposition between what Eurostat names "temporary contracts" and "open-ended contracts". On the other hand, because of the spreading of the effects of work and employment flexibilisation into new countries, new categories are appearing since the early 2000s (Prekariat, vulnerable workers, and even "precarity")."